2015
DOI: 10.1038/srep15971
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation-mediated interaction of SIRT1-HMGB1 improves survival in a mouse model of endotoxemia

Abstract: Inflammatory signal-mediated release of high-mobility group box 1 (HMGB1) is a damage-associated molecular pattern or alarmin. The inflammatory functions of HMGB1 have been extensively investigated; however, less is known about the mechanisms controlling HMGB1 release. We show that SIRT1, the human homolog of the Saccharomyces cerevisiae protein silent information regulator 2, which is involved in cellular senescence and possibly the response to inflammation, forms a stable complex with HMGB1 in murine macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 46 publications
3
106
0
Order By: Relevance
“…1C), although the majority of HMGB1 protein remained in the nuclear region (cytosol HMGB1; 19.5 ± 10.2 %, p < 0.05). These results were consistent with previous report [28], and suggested that HMGB1 released from nucleus is capable of inducing signal transduction. Moreover, using MAP2 to label neurons, and non-MAP2 positive stains to mark non-neuronal cells (i.e., astrocytes), HMGB1 translocation from the nucleus to the cytosol was comparable between neurons and astrocytes in the present mixed cell culture paradigm.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…1C), although the majority of HMGB1 protein remained in the nuclear region (cytosol HMGB1; 19.5 ± 10.2 %, p < 0.05). These results were consistent with previous report [28], and suggested that HMGB1 released from nucleus is capable of inducing signal transduction. Moreover, using MAP2 to label neurons, and non-MAP2 positive stains to mark non-neuronal cells (i.e., astrocytes), HMGB1 translocation from the nucleus to the cytosol was comparable between neurons and astrocytes in the present mixed cell culture paradigm.…”
Section: Resultssupporting
confidence: 83%
“…Because epilepsy, is a network disease, there is limited direct translational application of the present cell culture paradigm, which represents an artificial system with a specific number of neural subtypes. Nonetheless, the present results advance the concept of HMGB1 post-translational modifications [28, 55], in our understanding of disease pathology and developing treatments for epilepsy-related hyperexcitability.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we discovered that NR pretreatment markedly reduced plasma HMGB1 levels in septic mice, which correlated with an attenuation of lung injury and myocardial dysfunction in septic mice. Studies have demonstrated that hyper-acetylation of HMGB1 promotes its nucleus-to-cytoplasm translocation and release in activated immune cells [37]. SIRT1 induces de-acetylation of HMGB1 and thus, inhibits its release.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, RSV was found to effectively inhibit inflammatory responses by acting as a SIRT1 activator [25]. Some studies have shown that HMGB1 is a main downstream deacetylated target of SIRT1 [26] and SIRT1 activation inhibited HMGB1 secretion [27]. In contrast, some reports have claimed that SIRT1 inhibition, but not activation, could be a novel way to treat sepsis in its hypoinflammatory phase [28].…”
Section: Discussionmentioning
confidence: 99%